2020
DOI: 10.1039/d0re00085j
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten–zirconia-supported rhenium catalyst combined with a deoxydehydration catalyst for the one-pot synthesis of 1,4-butanediol from 1,4-anhydroerythritol

Abstract: Biomass-derived 1,4-anhydroerythritol is reduced to 1,4-butanediol over a reusable mixture of heterogeneous catalysts, ReOx–Au/CeO2 and ReOx/WO3–ZrO2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…In the case of ReO x -Au/CeO 2 + ReO x /WO 3 -ZrO 2 , the selectivities of the acetal, 2,5-dihydro-furan, tetrahydrofuran, and 1,4-butanediol were 37%, 26%, 22%, and 7%, respectively, at 45% conversion. 252 Furan, which is the byproduct co-produced by the disproportionation of dihydrofuran, was almost not formed. The higher levels of dihydrofuran and tetrahydrofuran selectivity at such low conversion suggested that dihydrofuran hydrogenation before hydration of dihydrofuran was the main formation route for tetrahydrofuran over ReO x -Au/CeO 2 + ReO x /WO 3 -ZrO 2 .…”
Section: Deoxydehydration (Dodh) and Dodh + Hydrogenation Of Erythritolmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of ReO x -Au/CeO 2 + ReO x /WO 3 -ZrO 2 , the selectivities of the acetal, 2,5-dihydro-furan, tetrahydrofuran, and 1,4-butanediol were 37%, 26%, 22%, and 7%, respectively, at 45% conversion. 252 Furan, which is the byproduct co-produced by the disproportionation of dihydrofuran, was almost not formed. The higher levels of dihydrofuran and tetrahydrofuran selectivity at such low conversion suggested that dihydrofuran hydrogenation before hydration of dihydrofuran was the main formation route for tetrahydrofuran over ReO x -Au/CeO 2 + ReO x /WO 3 -ZrO 2 .…”
Section: Deoxydehydration (Dodh) and Dodh + Hydrogenation Of Erythritolmentioning
confidence: 99%
“…In order to acquire catalyst reusability, the screening of oxides was conducted for the reaction of 2,5-dihydrofuran. 252 As a result, the ReO x /WO 3 -ZrO 2 catalyst showed a higher performance in the conversion of 2,5-dihydrofuran into 1,4-butanediol than other oxide-supported ReO x catalysts, although its performance was clearly lower than that of ReO x /C. Then, ReO x / WO 3 -ZrO 2 was used as a co-catalyst with ReO x -Au/CeO 2 for the one-pot conversion of 1,4-AHERY.…”
Section: Deoxydehydration (Dodh) and Dodh + Hydrogenation Of Erythritolmentioning
confidence: 99%
“…After the inspiring report of Trivedi et al., [181] which demonstrated for the first time the activity enhancement promoted by the synergic effect of the addition of other metals in Re 2 O 7 , Re‐based catalysts have been intensively explored [45,134,182–187] . Neurock et al.…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…Selective conversion of 1,4-anhydroerythritol is easier than that of erythritol itself because 1,4-anhydroerythritol has two different types of CÀ O bonds (ether and OH groups) while erythritol has four OH groups with similar reactivity. 1,4-Anhydroerythritol can be selectively converted into 1,4-butanediol, [11] 1,3-butanediol, [12] tetrahydrofuran, [13,14] 2-butanol, [15] and 2,5-dihydrofuran [16][17][18] by selective catalytic reduction. However, direct production of valuable chemicals from erythritol is still limited.…”
Section: Introductionmentioning
confidence: 99%